2016
DOI: 10.18178/ijlt.2.2.99-103
|View full text |Cite
|
Sign up to set email alerts
|

A Personalized E-Learning Based on Recommender System

Abstract: Personalized E-learning based on recommender system is recognized as one of the most interesting research field in the education and teaching in this last decade, since, the learning style is specific with each student. In fact from the knowledge his/her learning style; it is easier to recommend a learning scenario builds around a collection of the most adequate learning objects to give a better return on the educational level. This work focuses on the design of a personalized E-learning system based on a psyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 17 publications
1
20
0
2
Order By: Relevance
“…They were satisfied to learn with the preferred learner's profile and willing to use the system in the future. The results seem to support earlier studies which concluded that using learner profile matching with the learners' psychology is helpful to students in enhancing both learning efficacy and efficiency [8,11,29,30].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…They were satisfied to learn with the preferred learner's profile and willing to use the system in the future. The results seem to support earlier studies which concluded that using learner profile matching with the learners' psychology is helpful to students in enhancing both learning efficacy and efficiency [8,11,29,30].…”
Section: Resultssupporting
confidence: 87%
“…In this regard, several studies have been done to show if the personalized learning according to the learner profile can improve and enhance the performance of learning process. Results seem to be mixed [8,23,24], but most authors agree that taking into account the learning style in e-learning system could help learners to achieve an effective and efficient learning [11,24,29,30].…”
Section: Related Workmentioning
confidence: 99%
“…If it is added at that moment, the user might get a clue for specific possible reworking. In conclusion, there are circumstances where the effectiveness of the explanations can only judge if they have implemented in reality [12].…”
Section: Problems and Solutionmentioning
confidence: 96%
“…Adaptive presentation: content concepts are changing according to the student's needs. [10] proposed a personalized e-learning recommender system, called PERS, based on collaborative filtering recommendation to propose adaptive class materials that match student's needs based on group preferences. The cold start problem is solved using a static questionnaire per each new student base on Index Learning Style Questionnaire (ILSQ) to create initial model and initial recommendation.…”
Section: Content Modelmentioning
confidence: 99%